The Effects of the Socialization of Physical Education Teachers on Their Modes of Interaction With Students in Tunisian Schools - Nasri, Bechir; Kadri, Abdelmotaleb; Souissi, Nizar; Rouissi, Mourad (Frontiers in Sociology, 2022)
This article uses a combination of Bourdieu's concept of habitus theory and an interactionist perspective to address the socialization of physical education and sports teachers in a teaching setting in Tunisia. The two main objectives of the study are to present the social characteristics of the study population, draw general conclusions about the social origins of the Tunisian physical education and sports teachers, and to identify the link between socialization and the pedagogical practice of teachers of physical education in Tunisian schools. My colleagues an I collected data through participant observation and in-depth interviews with a representative sample of teachers. The results show that the socio-cultural origin, the type of training and the generational effect of the teachers of physical education and sports in a teaching setting at the Tunisian school influence the pedagogical behavior.